LEGAL MECHANISMS OF DIGITAL TRANSFORMATION IN THE ADMINISTRATIVE AND LEGAL REGULATION OF BANKING SERVICES - Kunishev Otabek Ruzibayevich (PEDAGOGS, 2025)
Abstract. This article comprehensively analyzes analyzes legal aspects of digital transformation in banking regulation. It compares global practices (Basel III, EU, US, Asia) and policies of international financial institutions (IMF, EBRD). Uzbekistan’s system is critically assessed, identifying gaps in supervision, stress-testing, and regulatory alignment. The paper recommends phased reforms, technological upgrades, enhanced global cooperation, and innovation adoption. The findings offer strategic directions for strengthening Uzbekistan’s banking sector resilience, aligning with international standards, and ensuring stability amid global financial integration.